Fundamentação judicial e o modelo Toulmin de argumentação: uma análise da fundamentação no novo código de processo civil brasileiro - Rocha, Duílio Lima (2015)
The lack of clarity and consistency in decisions makes common the convergence situation of different contexts for the same results with different arguments, although the obligation to state reasons court decisions constitutes, much more than a mere explanation or satisfaction for the parties, but a legitimate requirement of democratic rule of law in favor of the whole society and always striving for transparency and legal certainty. We seek to question the reasoning of the court decision concerning its necessarily sufficient rationality of content to be considered satisfied by constitutional rule, in Brazil the legal rule in Article 93, IX of the Constitution, identifying a minimum of coherence on behalf of expectation of rationality and predictability of the legal meaning of the decision, which has not occurred. We approach the notion of normative model of reasoning of judgments as a set of criteria against which to prove compliance or not of constitutional law imposing the obligation to state reasons for judgments. We identify the importance and the difficulties to be faced in building a normative model of reasoning of court decisions, as well as basic functions of a normative model of reasoning of court decisions, which will serve as an evaluation criterion of argumentation Toulmin model. We shall set out the essential features of the Toulmin model (lay out) and the main criticisms to which it is exposed, both in general and in its applicability to the right. Finally, we examine the relationship between the basis of criteria in the new Civil Procedure Code (Law 13.105/2015) and Toulmin model, thus analyzing the construction of a Brazilian normative model of reasoning of court decisions, in view of the completion of Fundamental Rights CF/88.